2008
DOI: 10.1002/adsc.200700283
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic Compounds by Samarium Diiodide‐Induced Cascade Cyclizations of Naphthyl‐Substituted 1,3‐Diones

Abstract: Treatment of naphthyl-substituted cyclopentane-1,3-diones with the samarium diiodidehexamethylphosphoramide (HMPA) complex in the presence of tert-butyl alcohol provided the expected tetracyclic diols with steroid-like structures. Surprisingly, reactions without the proton source led to the efficient formation of a new pentacyclic diol. In this case the toxic additive HMPA could be substituted by a combination of lithium bromide (in situ generation of samarium dibromide) and N,N-dimethylimidazolidone. The styr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The polycyclic compounds obtained under the reductive conditions reported above contain a styrene‐type double bond, which provides a suitable handle for subsequent synthetic transformations 3f,3i,3j. A few typical examples leading to highly functionalized compounds are presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The polycyclic compounds obtained under the reductive conditions reported above contain a styrene‐type double bond, which provides a suitable handle for subsequent synthetic transformations 3f,3i,3j. A few typical examples leading to highly functionalized compounds are presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…[12] However, it cannot be excluded that the reductive radical cyclization mechanism proceeds through an "arene-first" [4g] mechanism as suggested by Kise et al [19] It is believed that in a first step samarium ketyl B is formed in equilibrium from SmI 2 and indolyl ketone A. The ketyl radical B subsequently adds to the activated aromatic system through a six-membered transition state C. For steric and electronic reasons, the bulky samarium alkoxide, presumably bearing three or four ligands, is assumed to favor an equatorial position leaving the methyl group in an axial position.…”
Section: Mechanismmentioning
confidence: 97%
“…[10,11] In further consequence, we systematically investigated appropriately substituted ketones with aryl and naphthyl groups as acceptors for the electronrich ketyl radicals. [12] An obvious extension of the described SmI 2 -induced cyclization-dearomatization reaction involved the employment of N-heteroaromatic ring systems, such as quinoline, [13] pyrrole, and indole derivatives. [14] The general importance of N-heterocycles, of indole derivatives in particular, [15] originates from their ubiquitous presence in natural products and pharmaceutically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Reissig et al showed that treatment of the naphthyl-substituted cyclopentane-1,3-diones 79 (Scheme 32) with SmI 2 /HMPA in the presence of a proton donor could bring about the formation of the alcohols 80 with the steroid skeleton. [71] With the unsubstituted naphthalene moiety the reaction proceeded with good yield (70 %) and selectivity (α/β = 91:9).…”
Section: Other Transition-metal-mediated Processesmentioning
confidence: 98%